ANALYSIS OF THE HABITUATION OF RATIB SANTRI BUKI DHIKR AND ITS INFLUENCE ON THE SPIRITUAL AND EMOTIONAL INTELLIGENCE OF CONGREGATION MEMBERS - Ainul Izzah Ar Rofiq; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The increasingly complex dynamics of modern life have contributed to various emotional and spiritual challenges, highlighting the need for educational approaches that balance intellectual, emotional, and spiritual development. One such approach is the habituation of Ratib Santri Buki dhikr. This study aims to analyze the influence of Ratib Santri Buki dhikr habituation on the spiritual and emotional intelligence of its practitioners. The research employed a qualitative library research method. Data were collected through document studies from various academic sources, including books, scientific journals, research articles, and other relevant documents. Data analysis was conducted using content analysis techniques to identify, interpret, and synthesize findings from previous studies. The results indicate that the habituation of Ratib Santri Buki dhikr contributes significantly to the enhancement of spiritual intelligence by strengthening self-awareness, fostering closeness to Allah, creating inner peace, and helping individuals find deeper meaning in life. Furthermore, the practice also improves emotional intelligence by enhancing emotional regulation, reducing stress, increasing patience, and encouraging wiser responses to life’s challenges. Therefore, the habituation of Ratib Santri Buki dhikr can be regarded as a holistic Islamic educational method that effectively develops both spiritual and emotional intelligence in a balanced manner.